The skeletons in God's closet : the mercy of Hell, the surprise of judgment, the hope of holy war - Butler, Joshua Ryan. (Nashville, Tennessee : W Publishing Group, 2014)
There are some questions no Christian wants to be asked. Many today believe hell, judgment and holy war are "skeletons in God's closet," tough topics that, if looked at closely, would reveal a cruel, vindictive tyrant rather than a good and loving God. And we aren't comfortable with the answers we've been given.
Includes bibliographical information.
Keywords: End of the world; Hell -- Christianity; Judgment Day